The vanishing [videorecording (DVD)] - Sluizer, George; Donnadieu, Bernard-Pierre; Bervoets, Gene; Steege, Johanna ter; Krabbé, Tim (Criterion collection, 2001)
During a road trip with her husband, a woman is abducted by a methodical, calculating psychopath. Her husband becomes obsessed with learning her fate, and neither time nor the love of another woman can end his tormented quest.